Back to School: Upskilling Teachers’ Competence through Online Scholarship Workshop - Mahmud, Yogi Saputra; Kuhon, Richard; Slamet Santosa, Donald Samuel; Pujiastuti, Ani (International Journal of Community Service Learning, 2021)
As one of the strategic means of enhancing future competence and career, every individual, including teachers, is strongly encouraged to pursue a higher degree. Nevertheless, lack of financial ability may become one of the debilitating hindrances for the teachers to pursue a higher degree, mainly overseas. Currently, however, the Indonesian Government strives to support Indonesians to pursue a higher degree through a scholarship mechanism called the Indonesia Endowment Fund for Education, or popularly called as LPDP. Simultaneously, various scholarship mechanisms are also offered by several governing bodies in national or international contexts, such as Australia Awards, Chevening, Fulbright, DAAD, and many others. Therefore, this community empowerment project aims to enhance the understanding of schoolteachers, student-teachers, and other education communities regarding the administrative and technical preparation to register for a scholarship and prepare for overseas study. Moreover, the participants were also expected to comprehend the academic and social conditions while studying abroad, as well as the impact of pursuing a higher degree in their future competence and career. 535 participants were attending this community empowerment program in total.